2020
DOI: 10.3390/ma13020274
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of PLA-Micro-structured Hydroxyapatite Composite Films

Abstract: This article presents a facile synthesis method used to obtain new composite films based on polylactic acid and micro-structured hydroxyapatite particles. The composite films were synthesized starting from a polymeric solution in chloroform (12 wt.%) in which various concentrations of hydroxyapatite (1, 2, and 4 wt.% related to polymer) were homogenously dispersed using ultrasonication followed by solvent evaporation. The synthesized composite films were morphologically (through SEM and atomic force microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 44 publications
2
67
0
2
Order By: Relevance
“…The onset of degradation was also reduced for the most filled sample, showing a T 5% value of 254.8 °C, which represents a reduction of approximately 18 °C in comparison to the unfilled P(3HB- co -3HHx) sample and its nanocomposites at low contents. These results further indicate that the nanoparticles formed aggregates at high contents, which created volumetric gradients of concentration [ 66 ]. In this regard, Bikiaris et al [ 65 ] suggested that when high amounts of nanosized filler aggregates are formed, the structure shifts from nanocomposite to microcomposite and, thus, the shielding effect of the nanosized particles is lessened.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The onset of degradation was also reduced for the most filled sample, showing a T 5% value of 254.8 °C, which represents a reduction of approximately 18 °C in comparison to the unfilled P(3HB- co -3HHx) sample and its nanocomposites at low contents. These results further indicate that the nanoparticles formed aggregates at high contents, which created volumetric gradients of concentration [ 66 ]. In this regard, Bikiaris et al [ 65 ] suggested that when high amounts of nanosized filler aggregates are formed, the structure shifts from nanocomposite to microcomposite and, thus, the shielding effect of the nanosized particles is lessened.…”
Section: Resultsmentioning
confidence: 95%
“…The temperature at which the maximum mass loss rate occurred (T deg ) increased from 296.7 °C, for the neat P(3HB- co -3HHx) part, to 300.9 °C, for the part of P(3HB- co -3HHx) filled with 2.5 %wt of nHA. This increase in thermal stability has been previously ascribed to the formation of strong hydrogen interactions and Van der Walls forces between the inorganic nanoparticles and the biopolymer chains during the melt-mixing process [ 66 ]. The values of T deg remained nearly constant, showing no significant differences for nHA contents from 2.5 to 10 wt %, but it significantly decreased to 295.6 °C in the part filled with 20 wt % of nHA.…”
Section: Resultsmentioning
confidence: 95%
“…The current work aims to fill this gap, and attempts to carry out in vivo studies in addition to in vitro investigations to predict real-life applications in the biomedical field. Moreover, very few articles have been reported exploring the cytocompatibility of poly (lactic acid)/hydroxyapatite composites for the reconstruction of maxillofacial defects [ 26 , 27 , 28 ]. The present work deals with the preparation of porous PLA/HA scaffolds, and examines controlling their pore size by using solvent casting and a particulate leaching method.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks appear again with increasing the HA level. This could be explained by the fact that the presence of HA leads to a decrease in the crystallinity of PLA as the presence of these particles limits the mobility of PLA chains and decreases the orientation of polymer chains by increasing their degree of disorder [29]. This chain immobilization in the interphasial region results in a T g peak in the DSC curve for HA-containing samples [26].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%